Lacosamide as add-on treatment of focal symptomatic epilepsy in a patient with alcoholic liver cirrhosis - A. Romigi; F. Placidi; C. Liguori; F. Izzi; A. Marchi; E. Tarquini; M. Albanese; N.B. Mercuri (Epilepsy and Behavior Case Reports, 2014)
The occurrence of epileptic seizures in the presence of hepatic disease is not uncommon in clinical practice. Selecting an appropriate AED for patients affected by liver failure who have new-onset epileptic seizures can be challenging. We describe a 64-year-old man affected by liver cirrhosis. The patient developed partial epilepsy with secondary generalization because of an intracerebral hemorrhage in the left parieto-occipital regions. After the neurosurgery procedure, seizures reappeared and were initially managed with levetiracetam. After one month, the patient experienced clusters of seizures while on stable treatment with levetiracetam. Pregabalin as add-on was not tolerated; therefore, he received a low dose of phenobarbital as add-on treatment. The patient developed hepatic encephalopathy. Phenobarbital was immediately stopped, and oral lacosamide was added. A rapid recovery of encephalopathy with a 6-month seizure freedom was obtained. The patient died 6 months later because of progressive impairment of liver function. Lacosamide may represent an alternative to other AEDs in patients with liver failure; however, further prospective evaluation of its efficacy and safety in this clinical setting is needed.